Organizational Culture and the Turkish Military - R. Dilek KOÇAK; Sertif DEMİR (Gazi Akademik Bakış)
This paper examines the evolution of the organizational culture of Turkish military, and how underlying variables and dynamics have influenced its development. The main finding is that the Turkish military’s organizational culture includes shared basic norms, rules, values, and beliefs, and that they are taught to create a common identity to entrants. Turkish military organizational culture makes employees feel part of an exclusive organization where adherence to heroism, honor, patriotism, and loyalty represent a common identity. This paper includes three main sections: a brief theoretical overview of culture and organizational culture; analysis of the evolution of Turkish military culture; examination of the variables and dynamics influencing its evolution.